Comparing the levels of CTLA-4-dependent biological defects in patients with LRBA deficiency and CTLA-4 insufficiency - BARIŞ, SAFA; AYDINER, ELİF; ÖZEN, AHMET OĞUZHAN (My University, 2022)
Background Lipopolysaccharide-responsive beige-like anchor protein (LRBA) deficiency and cytotoxic T-lymphocyte protein-4 (CTLA-4) insufficiency are recently described disorders that present with susceptibility to infections, autoimmunity, and lymphoproliferation. Clinical and immunological comparisons of the diseases with long-term follow-up have not been previously reported. We sought to compare the clinical and laboratory manifestations of both diseases and investigate the role of flow cytometry in predicting the genetic defect in patients with LRBA deficiency and CTLA-4 insufficiency. Methods Patients were evaluated clinically with laboratory assessments for lymphocyte subsets, T follicular helper cells (T-FH), LRBA expression, and expression of CD25, FOXP3, and CTLA4 in regulatory T cells (Tregs) at baseline and 16 h post-stimulation. Results LRBA-deficient patients (n = 29) showed significantly early age of symptom onset, higher rates of pneumonia, autoimmunity, chronic diarrhea, and failure to thrive compared to CTLA-4 insufficiency (n = 12). In total, 29 patients received abatacept with favorable responses and the overall survival probability was not different between transplanted versus non-transplanted patients in LRBA deficiency. Meanwhile, higher probability of survival was observed in CTLA-4-insufficient patients (p = 0.04). The T-cell subsets showed more deviation to memory cells in CTLA-4-insufficiency, accompanied by low percentages of Treg and dysregulated cT(FH) cells response in both diseases. Cumulative numbers of autoimmunities positively correlated with cT(FH) frequencies. Baseline CTLA-4 expression was significantly diminished in LRBA deficiency and CTLA-4 insufficiency, but significant induction in CTLA-4 was observed after short-term T-cell stimulation in LRBA deficiency and controls, while this elevation was less in CTLA-4 insufficiency, allowing to differentiate this disease from LRBA deficiency with high sensitivity (87.5%) and specificity (90%). Conclusion This cohort provided detailed clinical and laboratory comparisons for LRBA deficiency and CTLA-4 insufficiency. The flow cytometric approach is useful in predicting the defective gene; thus, targeted sequencing can be conducted to provide rapid diagnosis and treatment for these diseases impacting the CTLA-4 pathway.
Keywords: Tıp; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Health Sciences; Natural Sciences; ALERJİ; Klinik Tıp; Klinik Tıp (MED); İmmünoloji; Yaşam Bilimleri (LIFE); ALLERGY; CLINICAL MEDICINE; Clinical Medicine (MED); IMMUNOLOGY; Life Sciences (LIFE); İmmünoloji ve Alerji; Genel İmmünoloji ve Mikrobiyoloji; Immunology and Allergy; Immunology; General Immunology and Microbiology; CTLA-4; inborn errors of immunity; LRBA; T follicular helper cells; Treg; REGULATORY T-CELLS; IMMUNE DYSREGULATION; MUTATIONS; DISEASE; DEMETHYLATION; ENDOCYTOSIS; PHENOTYPES; FAMILY; GENE; CTLA- 4; inborn errors of immunity; LRBA; T follicular helper cells; Treg